China’s influence on the Middle Eastern stance on Xinjiang : Case studies of Saudi Arabia and Iran - Gugo, Tea; Garlick, Jeremy; Přikryl, Pavel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
For years, Xinjiang has faced unrest affecting its Uyghur Muslim population, intensifying regional instability. The Chinese government suppresses separatist movements and "religious activities," restricting freedoms. Arab states denounce Xinjiang terrorist attacks and reject external interference, but individual reactions are often absent, a phenomenon this thesis explores. Despite ongoing Uyghur internment and Han Chinese influx, China persists with its policies, and the Middle East remains unlikely to intervene. This thesis aims to reveal the Uyghurs' struggle and investigate the Middle East's complicity, particularly Iran and Saudi Arabia, in China's control over Xinjiang. It asks: To what extent does the Middle East support China's interests at the expense of Uyghur Muslims? A qualitative review using various literature and case studies of Saudi Arabia and Iran, as well as their comparison, analyzes the geopolitical, economic, and diplomatic factors shaping their responses. The goal is to uncover patterns and contradictions in regional dynamics and contribute to academic and policy debates.
Vedoucí práce: Jeremy Alan Garlick
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses